Streams : their ecology and life - Cushing, C. E. (Colbert E.) (Academic Press, 2001)
Streams is a handbook that combines a discussion of the ecology of streams and rivers, in layperson language, with an illustrated field guide of the plants and animals found in running waters of North America. Various illustrations and maps accompany the text. The authors are extremely well known--Cushing is the lead content provider for an America On-Line service provided through Trout Unlimited entitled "Ask Dr. Cushing." He is frequently asked the sorts of questions that are answered in this field guide. J. David Allan is the author of a well known textbook in Aquatic Ecology